2003
DOI: 10.1109/tnano.2003.809120
|View full text |Cite
|
Sign up to set email alerts
|

Selective MOCVD growth of ZnO nanotips

Abstract: Abstract-ZnO is a wide bandgap semiconductor with a direct bandgap of 3.32eV at room temperature. It is a candidate material for ultraviolet LED and laser. ZnO has an exciton binding energy of 60 meV, much higher than that of GaN. It is found to be significantly more radiation hard than Si, GaAs, and GaN, which is critical against wearing out during field emission. Furthermore, ZnO can also be made as transparent and highly conductive, or piezoelectric. ZnO nanotips can be grown at relatively low temperatures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 11 publications
(15 reference statements)
1
58
1
2
Order By: Relevance
“…1 The combination of high excitonic and biexcitonic oscillator strength and good high temperature characteristics make ZnO a promising material for optical applications. 2 It has been used as a visible and ultraviolet photoconductor and as fluorescent material, apart from its usefulness in optical waveguides, acousto-optic devices, thin film transistors, etc. 3,4 Its wide band gap of 3.37 eV at room temperature makes ZnO suitable for shortwavelength optoelectronic devices, including light-emitting diodes ͑LEDs͒ and laser diodes ͑LDs͒.…”
mentioning
confidence: 99%
“…1 The combination of high excitonic and biexcitonic oscillator strength and good high temperature characteristics make ZnO a promising material for optical applications. 2 It has been used as a visible and ultraviolet photoconductor and as fluorescent material, apart from its usefulness in optical waveguides, acousto-optic devices, thin film transistors, etc. 3,4 Its wide band gap of 3.37 eV at room temperature makes ZnO suitable for shortwavelength optoelectronic devices, including light-emitting diodes ͑LEDs͒ and laser diodes ͑LDs͒.…”
mentioning
confidence: 99%
“…ZnO layers may take the form of nanostructures with complex shapes, e.g. nanorods, nanotubes, nanopropellers, nanoflowers, nanodots and nanotops, as shown in [16][17][18][19][20][21]. What more, they differ in their sensibility to effects of the gaseous environment.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of techniques including chemical vapor deposition (CVD), metalorganic chemical vapor deposition (MOCVD), thermal pyrolysis, etc. are generally used to synthesize zinc oxide (ZnO) nanoparticles and films [16][17][18]. In most of the cases, it is reported that ZnO nanostructures are resulted from epitaxial growth rather than isotropic nucleation.…”
Section: Introductionmentioning
confidence: 99%